Correlation of carotid intima medial thickness with triple vessel coronary artery disease - Shah, Adnan; Ayaz, Sair; Hussain , Iqbal; Banoori, Syed Anees; Ali, Jabar; Uddin , Syed Misbah (International Journal of Pathology, 2025)
Background: Coronary artery disease (CAD) is a leading cause of morbidity and mortality, with triple vessel disease (TVD) representing a severe and complex form. Carotid Intima-media thickness (CIMT) is a non-invasive marker of subclinical atherosclerosis and has been associated with cardiovascular risk. The aim of our study was to investigate the correlation between CIMT and TVD in patients at Lady Reading Hospital, assessing CIMT as a potential predictor for TVD. Methods: A cross-sectional study was conducted at the Department of Cardiology, MTI/Lady Reading Hospital, from June 1, 2023, to December 1, 2023. Seventy-four patients aged 30 to 70 years with a confirmed diagnosis of TVD were included using non-probability consecutive sampling. IMT was measured via B-mode ultrasound at six carotid artery sites. Pearson’s correlation coefficient was used to assess the relationship between CIMT and TVD, with stratification by age, gender, BMI, and disease duration. Results: The mean age of participants was 52.15 ± 5.617 years, with 74.3% males. TVD correlation was present in 62.2% of patients. Abnormal CIMT (>1 mm) was observed in 75.7% of participants. There was a significant positive correlation between CIMT and TVD (r = 0.312, p < 0.05), with stronger associations in older patients (r = 0.367) and females (r = 0.406). Conclusion: Increased CIMT is significantly correlated with the presence of TVD, suggesting its potential role in risk stratification for severe CAD particularly in older patients. These findings highlight the utility of CIMT as a non-invasive predictor for TVD, emphasizing the need for early screening and the targeted interventions for high-risk patients.